Determinants of Internal Control Disclosure and Its Impact on Company Value - Tri Jati, Andi; Wahyu Anggoro, Rusmawan (International Journal of Engineering and Technology, 2018)
The aims of this study were to examine the factors that affect the disclosure of the Internal Control Structure (ICS) and its impact on Corporate Value. Factors tested in this study were the size of the board of commissioners, the proportion of independent board of commissioners, board of commissioner’s meetings, the size of the audit committee and the audit committee meetings. This study was conducted using content analysis from the annual report of manufacturing companies in Indonesia from 2012-2016. The study found that the size of the board of commissioners, the proportion of independent board of commissioners, board of commissioners meetings, audit committee size had positive effect on the extent of ICS disclosure. Furthermore, the disclosure of ICS had been shown to increase the value of the company. Another finding was that audit committee meetings negatively affect the extent of ICS disclosure. Based on the above findings, it could be concluded that the board of commissioners and audit committees encourage companies to conduct ICS disclosure as a means of reducing agency problems. ICS disclosure proved to be used as a monitoring mechanism used by stakeholders in decision-making related to the company. Â Â